Occupied by Memory : the Intifada Generation and the Palestinian State of Emergency. - Collins, John (John Martin) (NYU Press, 2004)
Occupied by Memory explores the memories of the first Palestinian intifada. Based on extensive interviews with members of the "intifada generation," those who were between 10 and 18 years old when the intifada began in 1987, the book provides a detailed look at the intifada memories of ordinary Palestinians. These personal stories are presented as part of a complex and politically charged discursive field through which young Palestinians are invested with meaning by scholars, politicians, journalists, and other observers. What emerges from their memories is a sense of a generation ca.